2013
DOI: 10.1111/febs.12384
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional diversity in the activity and regulation of DAPK‐related protein kinases

Abstract: Within the large group of calcium/calmodulin-dependent protein kinases (CAMKs) of the human kinome, there is a distinct branch of highly related kinases that includes three families: death-associated protein-related kinases, myosin light-chain-related kinases and triple functional domain proteinrelated kinases. In this review, we refer to these collectively as DMT kinases. There are several functional features that span the three families, such as a broad involvement in apoptotic processes, cytoskeletal associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 86 publications
1
44
0
Order By: Relevance
“…These findings suggest that the molecular mechanism of kinase stretch activation is more complicated than first suspected, and may involve multiple other sites within titin (Ohlsson et al, 2012; Pfeffer et al, 2012). A more extensive review of the kinase domain can be found in Kontrogianni-Konstantopoulos et al (2009); Gautel (2011a); Temmerman et al (2013). …”
Section: Titin Architecture Within the Sarcomerementioning
confidence: 99%
“…These findings suggest that the molecular mechanism of kinase stretch activation is more complicated than first suspected, and may involve multiple other sites within titin (Ohlsson et al, 2012; Pfeffer et al, 2012). A more extensive review of the kinase domain can be found in Kontrogianni-Konstantopoulos et al (2009); Gautel (2011a); Temmerman et al (2013). …”
Section: Titin Architecture Within the Sarcomerementioning
confidence: 99%
“…STK17A (DRAK1) and STK17B (DRAK2) are more distantly related and less characterized members of the DAPK family [12-14]. DAPK1 is a multi-domain cytosolic actin filament-associated calcium/calmodulin-dependent, serine/threonine kinase that has a known regulatory role in cytoskeletal dynamics, apoptosis, autophagy, cell adhesion and motility [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these changes were noticeable as structural rearrangements at the DAPK-specific basic loop (residues 46-56), comprising the motif KRXXXXSRRG located at the upper lobe of the catalytic domain. The residues in this loop are highly exposed and face the catalytic site of DAPK (Temmerman et al, 2013). Besides this, there are significant structural rearrangements in the activation segment (residues 163-186), surface loops (residues 22-25 and 213-221) and in the N-terminal helix A (residues 8-12) of DAPK.…”
Section: Research Articlementioning
confidence: 99%